The United States Of America Withdrawal From Paris Agreement 2015: Desecuritization Of Climate - Shinta, Fardha Dewi; Jamilah, Maryam; Sinulingga, Anita Afriani (Mandala: Jurnal Ilmu Hubungan Internasional, 2022)
The climate change issue has become a great debate in U.S foreign policy. Starting from the year 1980, the United States considered climate change one of the nation's potential threats. It can be traced from the U.S's active participation in climate change international regimes. But in 2015, Donald Trump's administration decided to withdraw from Paris Agreement. This research describes the securitization effort of climate change in the Donald Trump Administration through the U.S withdrawal from the Paris Agreement. The analysis uses four political forms of de securitization of Lene Hansen; stabilization, replacement, re-articulation, and silencing. This research is qualitative with a descriptive analysis approach. This research found that the climate change de securitization in Donald Trump's administration uses the four political forms: stabilize climate change issues, replace climate change with the economic, immigrant, and terrorist Issues, and rearticulate the danger of other three subjects. However, it can be concluded that the silencing effort was not complete; it can be proved by establishing the U.S Coalition of societies (We are still in) which supports the Paris Agreement 2015, and some protests of the American public against Donald Trump's decision